2016
DOI: 10.1111/jfpp.12770
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Carob's Germ and Seed Peel as Natural Antioxidant Ingredients in Gluten-Free Crackers

Abstract: An antioxidant gluten-free cracker snack was developed through the inclusion of carob by-products (germ and seed peel). The levels of formulation of these two novel ingredients were optimized through their effect on nutritional, physicochemical, sensory and antioxidant parameters of the final product. The results showed that both ingredients affected significantly (P 0.05) the studied parameters. Based on the surface response models, germ content ranging 4-14% and seed peel lower than 9% were considered optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 50 publications
1
52
0
3
Order By: Relevance
“…Extracts were stored at −80 • C until use. TPCs were estimated using the Folin-Ciocalteu method as previously reported [12]. Gallic acid (GA) was used as the standard.…”
Section: Total Phenolic Content Determined By the Folin-ciocalteu Methodsmentioning
confidence: 99%
“…Extracts were stored at −80 • C until use. TPCs were estimated using the Folin-Ciocalteu method as previously reported [12]. Gallic acid (GA) was used as the standard.…”
Section: Total Phenolic Content Determined By the Folin-ciocalteu Methodsmentioning
confidence: 99%
“…The whole unprocessed fruit or its by-products, such as the germ, fruit extract, kibbles without seeds and the seed peel, have also been investigated by food technologists. Different parts of carob fruits have been used as food ingredients in bakery and confectionery products [17,18], as well as in fermented and non-fermented pastas due to their health-promoting properties [19,20,21]. Furthermore, researchers have attempted to formulate carob-based milk beverages and decoctions [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Total Phenol content (TP) was measured using the Folin–Ciocalteu method as described by Martín‐Diana et al (). Samples were diluted 1/10 (w/v) in methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Seeds are considered the most valuable part of the fruit, whereas carob's pulp (pod) and seed peel maybe considered as susceptible of valourization as food ingredients. Recent studies have revealed several physiological effects of carob fruit due to the presence of bioactive compounds that may be relevant to the prevention of chronic diseases including cancer, diabetes, hyperlipidemia and diarrhea (Goulas, Stylos, Chatziathanasiadou, Mavromoustakos, & Tzakos, ; Gruendel et al, ; Martín‐Diana et al, ; Zunft et al, ).…”
Section: Introductionmentioning
confidence: 99%